FDI Watch : Quarterly Report, Issue 3, June 2021 - World Bank (World Bank, Washington, DC, 2021)
The FDI Watch presents the latest data on foreign direct investment (FDI) flows and intentions, investor perceptions, and policy developments. It also highlights recent FDI publications by the World Bank and other organizations. This FDI watch quarterly report focuses on the activities as of June 2021.